(untitled) (Journal of Nepal Geological Society, 1998)
The study of aerial photographs and satellite images has revealed the youngest tectonic history of Nepal Himalaya. The nappes and thrust sheets piled up during the Alpinie orogeny are now breaking into smaller blocks and slide aside the northward pushing and subducting Indian Plate. Since the Pleistocene, faults are opening perpendicularly or obliquely to the regional trend, and blocks are moving laterally. Local pressure structures were developed by these movements. There is selective erosion in the regional synclines and anticlines of the Lesser Himalaya. The upper sections of the Higher Himalayan Crystalline and Tibetan Series are generally preserved in depressions on top of the Lesser Himalaya. The Lesser Himalayan rocks themselves are mainly outcrop in the antlclinal areas.